The early years of folk music : fifty founders of the tradition - Dicaire, David, 1963- (McFarland & Co., 2010)
"This history of folk music looks at musicians, collectors and other figures from around the world. The book presents an overview of international folk roots from the seventeenth century to the mid-twentieth century and shows the contributions of the artists and the evolution of folk music as a force for political and social change"--Provided by publisher.